STUDI KELAYAKAN LOKASI PUSAT DAUR ULANG PERSAMPAHAN KABUPATEN LANDAK - Pratiwi, Nana Novita (Jurnal Teknik Sipil, 2021)
Waste management with classical management (collect-transport-throw) in Landak Regency can not only cause aesthetic and environmental problems, but can also cause a large load on landfills. One alternative to solve the problem of solid waste is to build a waste recycling center. In order for the development to be right on target, it is necessary to carry out a location feasibility study in terms of physical and economic aspects. Thus, the aim of this research is to analyze the feasibility of waste recycling center location in Landak Regency. This research uses quantitative methods with scoring analysis. The results of the analysis concluded that the location classified as feasible to build a waste recycling center is the location in the Tebedak"™s landfills. Tebedak"™s landfills is considered feasible due to several factors, namely having sufficient area, long distance from settlements, fairly complete waste facilities, good accessibility, has the fastest payback period, an IRR value that is greater than the bank interest rate and has an NPV value and BCR 1.